Hubungan Hasil Belajar Elemen Gambar Teknis Dengan Kesiapan Kerja Sebagai Fashion Illustrator Siswa Kelas XI Fashion Design Di SMKN 1 Buduran Sidoarjo - Putri, Rosatias Tisa; Lutfiyah Hidayati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Vocational education plays a strategic role in preparing graduates to compete in the workforce, including in the fashion industry. As the fashion industry becomes increasingly complex, vocational high school graduates are expected to possess fashion illustration competencies that meet industry demands, one of which is the mastery of Technical Drawing Elements. This study aims to examine the relationship between learning outcomes in Technical Drawing Elements and work readiness as fashion illustrators among 11th-grade Fashion Design students at SMKN 1 Buduran Sidoarjo. The research employed a quantitative approach, with data collected through documentation of learning outcomes and a work readiness questionnaire, then analyzed using correlation techniques. The results indicate a positive and significant relationship between learning outcomes in Technical Drawing Elements and work readiness as fashion illustrators. These findings suggest that improved academic achievement can contribute to students’ work readiness, although other factors such as practical experience and psychological maturity also play a significant role. The implications of this study highlight the importance of industry involvement in strengthening students’ practical experience, as well as the need for more representative measurements of work readiness by involving alumni and employers to enhance student competencies in the field of fashion design.